Profile of patients of spontaneous pneumothorax of North Gujarat region, India: a prospective study at GMERS medical college, Dharpur-Patan - Rami, Kiran; Damor, Pradip; Upadhyay, Gunjan Paresh; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2017)
Background: Spontaneous pneumothorax is a respiratory emergency, which we come across in clinical practice. It needs quick diagnosis and prompt treatment. Its immediate and prompt management can save a life of the patient. Delayed management can produce serious implication on respiratory function. The objective was aimed to study profile of patients of spontaneous pneumothorax. Methods: This was a prospective descriptive study conducted among purposively selected 100 patients of pneumothorax at a GMERS Medical College and Hospital, Dharpur-Patan of North Gujarat region, India between February 2013 and January 2015 after taking written informed consent. A predesigned semi-structured performa was used. Detailed demographic and clinical data were recorded. Patients were treated with simple needle aspiration or Intercostal drainage tube (ICDT) as per the standard practice at our institute. Data was statistically analyzed using SPSS software (trial version). Results:Based on the total number of admissions to our hospital during the study period, the annual incidence of SP was calculated as 99.9 per 100,000 hospital admissions. Out of 100 patients 84 patients were above the age of 40 years. 96 % of the patients were male. Dyspnea was the most common symptom at the onset and was present in all patients. History of smoking was present in 88% of the patients. Past history of COPD and tuberculosis were found in 58% and 34% of the patients respectively. Radiological evidence showed right sided pneumothorax in 50% of the patients whereas 48% had left sided pneumothorax. 86% of the patients were treated with Intercostal drainage tube. Among all patients treated with ICDT, 6% of the patients had surgical emphysema while 10% of the patients had secondary infection of pleural space leading to hydro pneumothorax. Conclusion: Spontaneous pneumothorax in India is more often secondary to an underlying lung disease. COPD and pulmonary tuberculosis remains the common causes of SP. Smoking is an important risk factor for the development of pneumothorax. X-Ray chest is one of the most important investigations for diagnosis of pneumothorax & underlying etiological factors.